(untitled) (Fiep Bulletin - online, 2011)
One of the phases of the sportive orientation is the profiles identification, this way, all sports have a anthropometric, somatotype, dermatogliphics and physical aptitude profile that favors success, making more probable that someone with these characteristics have a better chance of success (FERNANDES FILHO, 2003; FILIN & VOLKOV, 1998). The CUMMINS & MIDLO (1961) Dermatogliphics Method has been utilized; somatotypical evaluation by the HEATH-CARTER (1967) technique; Maturational Auto-evaluation of the pubic hair by the Method proposed by TANNER (1962) and MATSUDO (2005); STANDING BROAD JUMP and SARGENT JUMP TEST has been done. The studied dermatogliphics characteristics were D10 = 12.5 ± 3.5 and TRC = 118.9 ± 43.1 in masculine students (n = 115) and D10 = 11.6 ± 4 and TRC = 107.5 ± 46.7 in feminine students (n = 80). The somatotypical characteristics were Endomorphism = 2.17 ± 1.11, Mesomorphism = 4.25 ± 1.50 and Ectomorphism = 3.48 ± 1.41(Meso-ectomorph) in the masculine group and Endomorphism = 3.96 ± 1.53, Mesomorphism = 3.79 ± 1.19 and Ectomorphism = 2.78 ± 1.24(Endomorph Mesomorph) in the feminine group. The strength were Vertical Jump= 41.5 ± 6.9 and Horizontal Jump = 192.9 ± 21.1 in the masculine group and Vertical Jump = 32.6 ± 6.7 and Horizontal Jump = 158.7 ± 28 in the feminine group. The Sexual Maturation has been P = 4.4 ± 0.8 in the masculine group and P = 4.7 ± 0.7 in the feminine group. The results were similar to the found by Barbosa et. al. (2007), Medina and Fernandes Filho (2002), Klein and Fernandes Filho (2003), Macêdo and Fernandes Filho (2003), Costa, Alves and Gomes (2006) and Fortes & Castro (2002). The studied students between 14 to 17 years of IFTO have show dermatogliphics, somatotypical, strength and sexual maturation characteristics compatibles with their age bracket.